2001
DOI: 10.1063/1.1415498
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of liquid crystal monolayers on polyimide alignment layers: A molecular dynamics simulation study

Abstract: Detailed atomistic molecular dynamics simulations were performed on monolayers of 4Ј-n-octyl-4-cyanobiphenyl ͑8CB͒ adsorbed onto a surface of poly-m-alkanpyromellitimide ͑poly-m-APM͒, where m is the number of CH 2 units between the imide moieties. Poly-3-APM and poly-4-APM surfaces served as model surfaces to investigate the influence of microscopic grooves, polar carbonyl groups exposed to the surface, and an anisotropic van der Waals interaction between the liquid crystal ͑LC͒ molecules and the polymer chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Other reasons, such as the influence of the combination rules for the polyimide-gas cross-term parameters 82 and the surface effect, 83 are currently being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Other reasons, such as the influence of the combination rules for the polyimide-gas cross-term parameters 82 and the surface effect, 83 are currently being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Correcting the potential energy only once still does not yet lead to a correct RDF. However, the process can be iterated until the potential V n (r) and the RDF n (r) generated from it are self-consistent, Equation (10).…”
Section: Continuous Models With Numerical Potentialsmentioning
confidence: 99%
“…MD simulations demonstrated that an aligned polyimide monolayer has the orientating ability for liquid crystal molecules. 32,33 Although the monolayer shows the atomic grooves on which the LC molecules are oriented, 33 the grooves are not as charged as those of PTFE. We presume that the difference in groove charge is the reason why a remarkable S ex value exceeding 0.95 has never been reported for polyimide.…”
Section: ¹1mentioning
confidence: 99%